1996
DOI: 10.1111/j.1365-2591.1996.tb01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Canal Finder and hand instrumentation in removal of gutta‐percha root fillings during root canal retreatment

Abstract: The purpose of this study was to quantify the amount of remaining gutta-percha/sealer on the canal walls when the Canal Finder system, hand instrumentation and a combination of both (hybrid technique) were used to remove these materials. The amount of apically-extruded debris and the time required for removal were also recorded. Sixty extracted maxillary anterior teeth were prepared using a stepback technique and obturated with gutta-percha. Reinstrumentation of all groups was done in conjunction with a solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 17 publications
4
48
0
7
Order By: Relevance
“…Finally, the evaluation of remaining filling material was performed by calculating the percentage of debris in the whole canal and in each third relative to the total canal area and to the area of each third. This method appears to be effective and supports previous studies performed by numerous investigators who demonstrated its efficacy in evaluating the amount of remaining filling materials (23,32). This procedure was undertaken to minimize the subjectivity that may be seen in evaluation methods using radiographs or photographs that are evaluated on a scoring system based on scales (21,33,34).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Finally, the evaluation of remaining filling material was performed by calculating the percentage of debris in the whole canal and in each third relative to the total canal area and to the area of each third. This method appears to be effective and supports previous studies performed by numerous investigators who demonstrated its efficacy in evaluating the amount of remaining filling materials (23,32). This procedure was undertaken to minimize the subjectivity that may be seen in evaluation methods using radiographs or photographs that are evaluated on a scoring system based on scales (21,33,34).…”
Section: Discussionmentioning
confidence: 50%
“…Other methods of gutta-percha removal include removing the coronal portion of gutta-percha using Gates Glidden or heat pluggers (4,18), then the rest can be removed by an ultrasonic technique (19,20). Additionally, rotary instruments can also be used, such as the inflexible GPX burs (18,21), the canal finder (22)(23)(24), or one of the recent flexible rotary nickel-titanium (NiTi) files in a slow-speed handpiece (25,26).…”
mentioning
confidence: 98%
“…Measurement of area covered by filling material remnants in the IMAGE TOOL 3.00 software. (7,15,(20)(21)(22)(23), NiTi rotary instruments (7,11,13,15,(24)(25)(26)(27)(28), and solvents (29)(30)(31). In this study, stainless steel K-type hand files and the ProTaper retreatment system with and without solvent were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques were performed by a single operator, which is an important factor during the comparison. 18 Solvents can also be used to dissolve the guttapercha points. Eucalyptol is a colorless solvent with an aromatic odor that is less irritating than chloroform and without carcinogenic potential.…”
Section: Discussionmentioning
confidence: 99%